How to succeed in the enterprise software market - Le Clair, Craig, 1953- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book describes enterprise-level information systems that businesses use to support their processes. It provides a clear and simple framework to help software companies understand this experience, and help them build software products compatible with organizations, humans, and complex customer environments. The book combines leading research on how technology affects humans and organizations with industry experience and case studies on enterprise software companies. It includes the inside story from case studies on emerging companies including OpenPages, E-Docs, ObjectStore, NewRiver, Inc. and other major buyers of IT services in the financial services industry. This book is a practical guide to results that bridge gaps between hard and soft science views of systems development, academic research, and actual practice.